Tembang dalam Tradisi Orang Sunda: Kajian Naskah Guguritan Haji Hasan Mustapa - Dede Burhanudin (Jurnal Lektur Keagamaan, 2013)
The content of Guguritan Haji Hasan Mustapa deals with the dynamic of religious life of Sundanese. Through,  Guguritan,  members of community communicate each other  by means of dialog. From the guguritan as a culture, it is manifestly that Sunda is an open cultural identity. Sunda and Sundanese also, have become the meeting point of their cultural identity. It was shown here by their pattern of reciprocal interaction and adaptation—both in group communication (makalangan) and  adaptation to the change of the world (ngigelan zaman dan ngigelkeun zaman).Keywords: Tembang,  Tradition, Guguritan Haji Hasan Mustapa